2019
DOI: 10.1016/j.bbmt.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice in Vitamin D Management in Allogeneic Hematopoietic Stem Cell Transplantation: A Survey by the Transplant Complications Working Party of the European Society for Blood and Marrow Transplantation

Abstract: Beyond its impact on bone health, numerous studies have investigated the immune-regulatory properties of vitamin D and shown how its deficiency can affect outcomes in allogeneic hematopoietic stem cell transplantation (HSCT), particularly in acute or chronic graft-versus-host disease. This survey, carried out by the Transplant Complications Working Party of the European Society for Blood and Marrow Transplantation (EBMT), describes the current clinical practice discrepancies across the EBMT HSCT programs. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Despite conflicting results, pediatric studies often report that VDD is not associated with aGVHD, rather related with cGVHD and low survival rates 3,4,18 a statement with which the findings of this study conflict: where only one patient died (Table 1) and no association was found with cGVHD. One plausible explanation for this difference can be that all other studies 3,6,8,12,17 included patients with various malignant and non‐malignant conditions with different baseline problems such as leukemias and immunodeficiencies prior to HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite conflicting results, pediatric studies often report that VDD is not associated with aGVHD, rather related with cGVHD and low survival rates 3,4,18 a statement with which the findings of this study conflict: where only one patient died (Table 1) and no association was found with cGVHD. One plausible explanation for this difference can be that all other studies 3,6,8,12,17 included patients with various malignant and non‐malignant conditions with different baseline problems such as leukemias and immunodeficiencies prior to HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary objective was to determine the frequency of chronic GVHD (cGVHD), the presence of alloimmunization, total days of hospitalization, chimerism, and survival at the last follow‐up. As post HSCT vitamin D levels are not routinely checked in this treatment setting in line with current clinical practices, 12 vitamin D 3 levels were recorded in 50 patients mostly in the 3rd month after HSCT as this is the point at which vitamin levels were mostly measured.…”
Section: Methodsmentioning
confidence: 99%
“…There is data in the literature that recommend the use of supplements with vitamins and amino acids in order to increase immunity and reduce inflammation and oxidative stress 209 . It has a meta-analysis published in 2016 that assesses the impact of this supplementation on the incidence of GVHD and infections associated with HSCT 210 .…”
Section: Vitamin and Mineral Supplementation In Pediatric Patients After Hsctmentioning
confidence: 99%
“…Patients receiving vitamin supplementation had a 19% decrease in the incidence of GVHD and there was no significant difference in the incidence of infections. The conclusion of the study was that the use of these supplements is associated with a reduced risk of GVHD probably as a result of better immune support and elimination of free radicals 209 . However, although the results of this meta-analysis are significant, there are limitations to this study, including the fact that the patient sample is relatively small.…”
Section: Vitamin and Mineral Supplementation In Pediatric Patients After Hsctmentioning
confidence: 99%
See 1 more Smart Citation